2020
DOI: 10.3390/antiox9020152
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Chemotypic Variation on the Anti-Oxidant and Anti-Cancer Activities of Sutherlandia frutescens (L.) R.Br. (Fabaceae) from Different Geographic Locations

Abstract: Extracts of Sutherlandia frutescens (cancer bush) exhibit considerable qualitative and quantitative chemical variability depending on their natural wild origins. The purpose of this study was thus to determine bioactivity of extracts from different regions using in vitro antioxidant and anti-cancer assays. Extracts of the species are complex and are predominantly composed of a species-specific set of triterpene saponins (cycloartanol glycosides), the sutherlandiosides, and flavonoids (quercetin and kaempferol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Other studies revealed IC 50 values higher than 100 µg/mL. For example, in the study of Zoyane et al (2020) [ 15 ] with S. frutescens extracts produced from plants growing at different geographic localities in South Africa, IC 50 values confirmed the relatively higher potency of plants from Colesburg, Zastron, and Gansbaai 1 (158.7, 172.7, and 176.7 µg/mL, respectively) [ 15 ]. Furthermore, in the study of Izuegbuna et al (2019) [ 17 ], the acetone-dried extract of O. stricta showed mild cytotoxicity (IC 50 = 110.1 µg/mL), and Unuofin et al (2018) [ 18 ] showed IC 50 values for aqueous and ethanol extracts of K. africana > 200 µg/mL.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Other studies revealed IC 50 values higher than 100 µg/mL. For example, in the study of Zoyane et al (2020) [ 15 ] with S. frutescens extracts produced from plants growing at different geographic localities in South Africa, IC 50 values confirmed the relatively higher potency of plants from Colesburg, Zastron, and Gansbaai 1 (158.7, 172.7, and 176.7 µg/mL, respectively) [ 15 ]. Furthermore, in the study of Izuegbuna et al (2019) [ 17 ], the acetone-dried extract of O. stricta showed mild cytotoxicity (IC 50 = 110.1 µg/mL), and Unuofin et al (2018) [ 18 ] showed IC 50 values for aqueous and ethanol extracts of K. africana > 200 µg/mL.…”
Section: Discussionmentioning
confidence: 94%
“…Different assays were performed to evaluate the cytotoxicity effects of the studied African plant extracts, including a crystal violet cell antiproliferation assay [ 29 ], resazurin reduction assay [ 20 , 21 , 22 , 25 , 34 ], or tetrazolium-based colorimetric cell proliferation assays such as MTT [ 14 , 16 , 17 , 19 , 23 , 26 , 28 , 29 , 30 , 31 , 33 ], MTS [ 32 ] and WST-1 [ 13 ]. There were studies where cell numbers were determined using Hoechst 33342/Propidium Iodide (PI) staining [ 12 , 18 ], trypan blue [ 24 ], or were based on the quantification of Adenosin Triphosphate (ATP), signaling the presence of metabolically active cells [ 15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a previous study in Caco-2 cells cultured in 2D demonstrated induction of apoptosis following treatment for 48 h, but the study used an ethanolic extract [ 30 ]. Cytotoxicity of S. frutescence was also confirmed in DLD-1 colon cancer cells cultured in 2D, with IC 50 values between 150 and 180 µg·mL −1 [ 31 ]. Furthermore, unlike paclitaxel, treatment with S. frutescens does not appear to induce gene expression of the CYP3A4 and CYP2D6 enzymes but rather maybe inhibits expression.…”
Section: Discussionmentioning
confidence: 99%